Fronto-Parietal Brain Areas Contribute to the Online Control of Posture during a Continuous Balance Task. (10th August 2019) - Goel, Rahul; Nakagome, Sho; Rao, Nishant; Paloski, William H.; Contreras-Vidal, Jose L.; Parikh, Pranav J.
Abstract: Neuroimaging studies have provided evidence for the involvement of frontal and parietal cortices in postural control. However, the specific role of these brain areas for postural control remains to be known. Here, we investigated the effects of disruptive transcranial magnetic stimulation (TMS) over supplementary motor areas (SMA) during challenging continuous balance task in healthy young adults. We hypothesized that a virtual lesion of SMA will alter activation within the brain network identified using electroencephalography (EEG) and impair performance of the postural task. Twenty healthy young adults received either continuous theta burst stimulation (cTBS) or sham stimulation over SMA followed by the performance of a continuous balance task with or without somatosensory input distortion created by sway-referencing the support surface. cTBS over SMA compared to sham stimulation showed a smaller increase in root mean square of center of pressure as the difficulty of continuous balance task increased suggestive of altered postural control mechanisms to find a stable solution under challenging sensory conditions. Consistent with earlier studies, we found sources of EEG activation within anterior cingulate (AC), cingulate gyrus (CG), bilateral posterior parietal regions (PPC) during the balance task. Importantly, cTBS over SMA compared to sham stimulation altered EEG power within the identified fronto-parietal regions. These findings suggest that the changes in activation within distant fronto-parietal brain areas following cTBS over SMA contributed to the altered postural behavior. Our study confirms a critical role of AC, CG, and both PPC regions in calibrating online postural responses during a challenging continuous balance task. Highlights: Frontal and parietal brain areas are active during balance instability. Disruption of supplementary motor area or SMA affected balance behavior. SMA disruption affected the function of activated brain areas. Frontal and parietal brain areas are critical for the control of balance.